Genetic mutations in epigenetic modifiers as therapeutic targets in acute myeloid leukemia. (September 2015) - Nebbioso, Angela; Benedetti, Rosaria; Conte, Mariarosaria; Iside, Concetta; Altucci, Lucia
<x xml:space="preserve">Abstract</x> Introduction: Despite enormous insights into the molecular mechanisms of acute myeloid leukemia (AML) pathophysiology, this disease is still fatal in the majority of patients, highlighting the urgent need for novel biomarkers useful in AML prognosis and therapy. Areas covered: The advent of modern sequencing technologies has allowed the identification of genetic mutations in genes encoding for specific enzymes involved in the epigenetic regulation of gene expression. The authors review recent data demonstrating the involvement of mutations in genes encoding for epigenetic players and their complex combination with somatic genetic mutations in the pathogenesis of AML. They also discuss the prognostic and therapeutic implications of these findings. Expert opinion: Current clinical and preclinical studies are underscoring the importance of targeting epigenetic modifiers as new biomarkers for a better prognostic risk stratification and therapeutic evaluation of intermediate-risk patients. Combining data from traditional and modern methodologies will allow a definition of the complex networks of epigenetic changes and molecular interactions between candidate epitargets and key regulators of hematopoiesis. It will thus be possible to achieve an overview of potential aberrant mechanisms driving leukemogenesis in different classes of AML patients. Such an improved approach could pave the way towards 'personalized' therapies.